Embedding Librarianship Practices: A Case Study of Faculty of Pharmacy Embedded Librarian, University of Maiduguri - Samaila , Inuwa; Emmanuel , Camble (MiddleBelt Journal of Library and Information Science, 2020)
It is essential for academic libraries to continue to change their roles and establish deep contacts through the University to uphold and advocate their importance to all patrons. Embedded roles in research and teaching, and an embedded librarian’s existence in the faculties/departments will strengthen the academic library’s presence within its parent institution. The focus of this paper is to reflect on Embedding Librarianship Practices at the Faculty of Pharmacy, University of Maiduguri, Nigeria. The authors employed face to face interview with the Faculty embedded librarian. The findings of the study indicated that the role of the embedded librarian include teaching information literacy to undergraduate students, offer research assistance, promoting current, new and innovative library services to users, providing information at the point of needs, serve on faculty committee, and strengthening collaboration between faculty and the central library. The research has shown that in order for librarians to be effective in the learning community, this study point to the continued need for collaboration between librarians and teaching faculties.